Soil–plant–atmosphere conditions regulating convective cloud formation above southeastern US pine plantations. (25th March 2016) - Manoli, Gabriele; Domec, Jean‐Christophe; Novick, Kimberly; Oishi, Andrew Christopher; Noormets, Asko; Marani, Marco; Katul, Gabriel
Abstract: Loblolly pine trees ( Pinus taeda L.) occupy more than 20% of the forested area in the southern United States, represent more than 50% of the standing pine volume in this region, and remove from the atmosphere about 500 g C m − 2 per year through net ecosystem exchange. Hence, their significance as a major regional carbon sink can hardly be disputed. What is disputed is whether the proliferation of young plantations replacing old forest in the southern United States will alter key aspects of the hydrologic cycle, including convective rainfall, which is the focus of the present work. Ecosystem fluxes of sensible ( H s ) and latent heat (LE) and large‐scale, slowly evolving free atmospheric temperature and water vapor content are known to be first‐order controls on the formation of convective clouds in the atmospheric boundary layer. These controlling processes are here described by a zero‐order analytical model aimed at assessing how plantations of different ages may regulate the persistence and transition of the atmospheric system between cloudy and cloudless conditions. Using the analytical model together with field observations, the roles of ecosystem H s and LE on convective cloud formation are explored relative to the entrainment of heat and moisture from the free atmosphere. Our results demonstrate that cloudy–cloudless regimes at the land surface are regulated by a nonlinear relation between the Bowen ratio Bo = H s / LE and root‐zone soil water content, suggesting that young/mature pines ecosystems have the ability to recirculate available water (through rainfall predisposition mechanisms). Such nonlinearity was not detected in a much older pine stand, suggesting a higher tolerance to drought but a limited control on boundary layer dynamics. These results enable the generation of hypotheses about the impacts on convective cloud formation driven by afforestation/deforestation and groundwater depletion projected to increase following increased human population in the southeastern United States.